Electrocambalidae fam. nov., a new family of Cambalidea from Cretaceous Burmese amber (Diplopoda, Spirostreptida) - Moritz, Leif; Wesener, Thomas (European Journal of Taxonomy, 2021)
A new family, Electrocambalidae fam. nov. of the suborder Cambalidea is described from Cretaceous Burmese amber based on two new genera, Electrocambala gen. nov. and Kachincambala gen. nov. with four new species, Electrocambala ornata gen. et sp. nov., E. cretacea gen. et sp. nov., Kachincambala muelleri gen. et sp. nov. and K. distorta gen. et sp. nov. The specimens are described combining classical light microscopy with drawings and photography, and modern micro-computed tomography (μCT). Morphological characters otherwise obscured are examined and visualized by creating volume renderings and 3D-segmentations from μCT data. Electrocambalidae fam. nov. is characterized by the following character combination: (1) a forward shift of leg pair 3, resulting in an apparently legless 3rd body ring, (2) presence of metazonital setae, and (3) extensive pilosity on the head. Although some of these characters are shared with other Juliformia they are unique in this combination. The described fossils are the oldest and first Mesozoic Spirostreptida and Cambalidea known and ca 70 million years older than previous records of the group.